Article 3: Characterization of the stress-induced gene ZmCOI6.1 in maize: Expression and promoter sequences - Ha, Nguyen Thuy; Leipner, JÖrg; Guerra-Peraza, Orlene; Stamp, Peter (Academia Journal of Biology, 2014)
Using cDNA subtraction technique, 18 cold stress responsive-genes were identified, among them a novel gene, ZmCOI6.1, whose function is still unknown. Analysis of the ZmCOI6.1 promoter sequence revealed several conserved stress-responsive cis-acting elements. Further expression characterization shows that ZmCOI6.1 is induced, in addition by cold, by other abiotic stresses such as drought and NaCl as well as by signalling molecules such as ABA and SA. The results indicate that ZmCOI6.1 is a general stress responsive gene. A possible regulation mechanism is presented where ZmCOI6.1 is alternatively spliced yielding two transcripts whose levels are changed upon different stress treatments. Furthermore the predicted ZmCOI6.1 amino acid sequence and its homologue show high similarity with proteins in rice and Arabidopsis suggesting that it belongs to a conserved protein in plants